(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: The COVID-19 pandemic posed unique challenges to healthcare professionals (HCPs) with increased risk of mental health and well-being globally. However, the psychological impact of the pandemic on the mental health and well-being of HCPs in Canada is not fully understood. This paper critically reviews broadly available literature on the mental health and psychosocial status of HCPs amid the COVID-19 pandemic in Canada. Methods: A comprehensive online search was conducted using the guidelines outlined by the Centre for Reviews and Dissemination for combining the findings of diverse primary studies within a single review. Online search was conducted through databases such as AMED (Allied and Complementary Medicine), Embase, Global Health, Ovid Healthstar, Mental Measurements Yearbook, EBM Reviews - ACP Journal Club, EBM Reviews - Cochrane Database of Systematic Reviews, Ovid MEDLINE(R) and Epub Ahead of Print, In-Process, In-Data-Review, and Google Scholar for the period between March 2020 and May 2023. Twenty-two studies met the inclusion criteria and were analyzed systematically using a thematic analysis approach to identify the main themes across studies. Results: The analysis uncovers three key themes: 1) HCPs face diverse mental health impacts during the pandemic; 2) HCPs are dissatisfied with organizational approaches to COVID-19; and 3) HCPs express concerns about personal well-being and the safety of others during the pandemic. Conclusion: These findings emphasize the need for HCPs to cope effectively with stressors for their own, their patients, and their families’ well-being. Therefore, future research should prioritize the ways in which HCPs can maintain their emotional, mental, and psychological well-being.